2018
DOI: 10.1097/scs.0000000000004299
|View full text |Cite
|
Sign up to set email alerts
|

Safety Outcomes in Endoscopic Versus Open Repair of Metopic Craniosynostosis

Abstract: In our patient population, endoscopic surgery for metopic craniosynostosis had an improved safety profile versus open surgery based on reduced procedure length, estimated blood loss, volume of blood transfusion, and length of stay in the ICU and hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Most of the sutures involved were the anterior sutures (metopic and coronal). The mean age at surgery in the endoscopic group was 3.7 months (3-5) and higher at 11.5 months (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) in the open group (P < .05). The duration of surgery, blood loss and overall length of hospital stay were significantly reduced in the endoscopic group (P < .05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Most of the sutures involved were the anterior sutures (metopic and coronal). The mean age at surgery in the endoscopic group was 3.7 months (3-5) and higher at 11.5 months (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) in the open group (P < .05). The duration of surgery, blood loss and overall length of hospital stay were significantly reduced in the endoscopic group (P < .05).…”
Section: Resultsmentioning
confidence: 91%
“…[7][8][9][10] Minimally invasive techniques are gaining popularity due to their short incisions, reduced morbidity, quick recovery and relative safety. [7][8][9][10] In developing countries, internet penetration is increasing, along with increased acceptance of new technologies. Parents are using FACE 1 (2) the internet to research latest technical advances and are keen to seek treatment early.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical advantages of endoscopic treatment of craniosynostosis over open CVR have been well documented and include decreased operative blood loss and transfusion requirements, as well as shorter operative times and LOS. 1,6,10,13,14,18,21,31,39 An increasing body of literature from our institution and others has demonstrated promising outcomes in cranial morphology after EAC FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic techniques combined with postoperative molding helmet therapy have shown promising postoperative outcomes, with the benefits of reductions of the following: blood loss, transfusion requirement, operative time, and duration of hospitalization. 1,6,10,13,14,18,21,31,39 The endoscopic approach is becoming an increasingly appealing alternative to traditional open reconstructions. Concurrently, there has been increasing interest in the discrepancy in the costs of these two significantly different surgical approaches to the same cranial malformation.…”
mentioning
confidence: 99%
“…In a recent report Challenges comprised: the small scalp incision, long distance from incision to nasofrontal suture, presence of venous perforators from the sagittal sinus, and the narrow osteotomy corridor (5 mm). Most authors shared these observations and point of view concerning early cosmetic results [29][30][31][32][33][34][35]. Others analyzed their long-term results using a microscopic minimally invasive approach and concluded that it was not appropriate for trigonocephaly, and therefore stopped using this technique in these patients [31].…”
Section: Endoscopic and Microscopic Minimally Invasive Approachesmentioning
confidence: 95%